Análisis de las secuencias codificantes de los genes relacionados con la respuesta inmunitaria a los parásitos cestodos - Cueva Luje, Dayana Lisseth (2021)
In this research, a database was created form the analysis of the genetic sequences of the cestodes parasites gene, the information previously used by Biotechnologists is used to elaborate a specific DNA vaccine of each parasite, it will be given to know the characteristics that are generating immunity in the different domestic species, for which, information was obtained from the genetic sequences of each of these genes: EgAgB (canines), Th1 (canines and horses), NC2 (canines, goats) , Th2 (guinea pigs) Ts45W (cattle), To45W (sheep), Tbx6 (canines, goats and sheep, Th2 IL4 / IL5 (pigs) and RT10CDNA (birds). We investigated, collected information and validated on “National Center for Biotechnology Information" webpage, once the data was validated, it was able to create a database with the following: gene, animal species, chromosome / location, exon / intron, protein sequence, immunity and pathology. This database will contribute to and encourage the first investigations of genetic sequences, as well as the elaboration and verification one with the immunity to animals at the elaboration of the DNA vaccine. Were analyzed 33 genes from which complete information was obtained from 41% of the genes and 53% with incomplete data.